Interferon regulatory factor 5 (IRF5) gene variants are associated with multiple sclerosis in three distinct populations. Issue 6 (19th February 2008) - Kristjansdottir, G; Sandling, J K; Bonetti, A; Roos, I M; Milani, L; Wang, C; Gustafsdottir, S M; Sigurdsson, S; Lundmark, A; Tienari, P J; Koivisto, K; Elovaara, I; et al.
Abstract : Background: IRF5 is a transcription factor involved both in the type I interferon and the toll-like receptor signalling pathways. Previously, IRF5 has been found to be associated with systemic lupus erythematosus, rheumatoid arthritis and inflammatory bowel diseases. Here we investigated whether polymorphisms in the IRF5 gene would be associated with yet another disease with features of autoimmunity, multiple sclerosis (MS). Methods: We genotyped nine single nucleotide polymorphisms and one insertion-deletion polymorphism in the IRF5 gene in a collection of 2337 patients with MS and 2813 controls from three populations: two case–control cohorts from Spain and Sweden, and a set of MS trio families from Finland. Results: Two single nucleotide polymorphism (SNPs) (rs4728142, rs3807306), and a 5 bp insertion-deletion polymorphism located in the promoter and first intron of the IRF5 gene, showed association signals with values of p<0.001 when the data from all cohorts were combined. The predisposing alleles were present on the same common haplotype in all populations. Using electrophoretic mobility shift assays we observed allele specific differences in protein binding for the SNP rs4728142 and the 5 bp indel, and by a proximity ligation assay we demonstrated increased binding of the transcription factor SP1 to the risk allele of the 5 bp indel. Conclusion: These findings add IRF5 to the short list of genes shown to be associated with MS in more than one population. Our study adds to the evidence that there might be genes or pathways that are common in multiple autoimmune diseases, and that the type I interferon system is likely to be involved in the development of these diseases.